Tests of the prototype of a universal saddle for drilling water supply pipelines - Duklewski, Wiesław; Kępiński, Kamil; Mierzwa, Aneta; Iwanek, Małgorzata; Kowalska, Beata; Kowalski, Dariusz; Kwietniewski, Marian (Instal, 2020)
This study is a continuation of an article published in the INSTAL journal (No. 3/2018). It presents a prototype of a new universal saddle for pipe drilling, integrated with a knife cut-off valve. The presented saddle can be used for a wide range of diameters and materials of pipelines. The knife cut-off valve integrated with it eliminates the need for an additional standard valve. It also reduces the distance between the upper edge of the saddle and the center of the pipe, which is important during installing various types of monitoring sensors. The prototype built by the Tool Workshop of the Fabyka Łożysk Tocznych – Kraśnik S.A. has been successfully subjected to tightness tests in laboratory conditions.
Keywords: water supply; pipe drilling; universal saddle